Hyperscale and microcare : the digital business cookbook - Verhasselt, Peter, ....-; Boucart, Nick, ....- (Brugge : Die Keure, 2018)
In this book, Peter Verhasselt and Nick Boucart will explore what it takes to build winning digital products today. They'll focus on the idea that one should stop building software, and build digital services instead, effectively combining hyperscale with microcare: the ability to establish an intimate relationship with each and every of your thousands of users. Peter and Nick will discuss the capabilities and processes you need to build such digital services. They zoom in on the kinds of assets you need to develop, and that will greatly influence the valuation, all supported with practical advice and real world examples.
Keywords: Business ; digital; Digital products; Organisatiekunde